AN ANALYSIS OF THE SYMBOLIC MEANING ON TIJAK TANAH TRADITION IN MALAY SOCIETY - Selvianingsih, Selvianingsih; Bahari, Yohanes; Ismiyani, Nining; Le, Minh Tan (Universitas Tanjungpura, 2023)
This study aims to describe the symbolic meanings that exist in the Tijak Tanah tradition and the procession of the Tijak Tanah tradition in the Malay community in Sungai Nanjung Village, Ketapang Regency. The data sources for this research are the elders in Sungai Nanjung Village, people who usually recite Al-Barzanji, traditional leaders, two communities who have carried out the Tijak Tanah tradition and village staff in Sungai Nanjung Village. Retechniques used for the data collection were interview, observation and documentation methods. The results of the research showed that in the Tijak Tanah tradition the symbols used had meanings such as the sugar cane house symbol which has a meaning as a substitute for baby's feet and hands, but has a meaning to attach illness, coconut water and scissors mean that children are not weak in spirit, 12 eggs mean the spirit of a baby paid for with money, beads mean a form of beauty, and scattered rice means gratitude. The procession for the Tijak Tanah tradition is divided into 3 processes, namely the initial, core and final processes. The initial process is to prepare everything needed for the event, The main process is the top event when the baby is cut into his hair so that his feet are planted on the ground. The final process is reading prayers and eating together.